Efficacy of early controlled motion of the ankle compared with no motion after non-operative treatment of an acute Achilles tendon rupture: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Barfod, Kristoffer; Hansen, Maria; Holmich, Per; Troelsen, Anders; Kristensen, Morten
Abstract Background Early controlled ankle motion is widely used in the non-operative treatment of acute Achilles tendon rupture, though its safety and efficacy have never been investigated in a randomized setup. The objectives of this study are to investigate if early controlled motion of the ankle affects functional and patient-reported outcomes. Methods/design The study is performed as a blinded, randomized, controlled trial with patients allocated in a 1:1 ratio to one of two parallel groups. Patients aged from 18 to 70 years are eligible for inclusion. The intervention group performs early controlled motion of the ankle in weeks 3–8 after rupture. The control group is immobilized. In total, 130 patients will be included from one big orthopedic center over a period of 2½ years. The primary outcome is the patient-reported Achilles tendon Total Rupture Score evaluated at 12 months post-injury. Secondary outcome measures are the heel-rise work test, Achilles tendon elongation, and the rate of re-rupture. The primary analysis will be conducted as intention-to-treat analyses. Discussion This trial is the first to investigate the safety and efficacy of early controlled motion in the treatment of acute Achilles tendon rupture in a randomized setup. The study uses the patient-reported outcome measure, the Achilles tendon Total Rupture Score, as the primary endpoint, as it is believed to be the best surrogate measure for the tendon's actual capability to function in everyday life. Trial registration ClinicalTrials.gov:NCT02015364 . Registered on 13 December 2013.